Buying behavior of consumers in social networks: motives and performance indicators - Strashynska, Larysa; Strashynskyi, Volodymyr (My University, 2024)
The essence of the motives of the purchasing behavior of consumers in social networks has been determined. Their classification and main characteristics are given. A set of indicators for studying the effectiveness of marketing behavior of an enterprise in social networks is substantiated

Визначено сутність мотивів купівельної поведінки споживачів у соціальних мережах. Наведено їх класифікацію та основні характеристики. Обґрунтовано сукупність показників вивчення результативності маркетингової поведінки підприємства в соціальних мережах
Keywords: social networks; purchasing behavior; consumer demand; online shopping; online shopping; online stores; кафедра маркетингу; соціальні мережі; купівельна поведінка; споживчий попит; он-лайн покупки; інтернет-магазини